2005
DOI: 10.1080/02827580500251432
|View full text |Cite
|
Sign up to set email alerts
|

TransgenicBetula pendulaexpressing sugar beet chitinase IV forms normal ectomycorrhizae withPaxillus involutus in vitro

Abstract: Mycorrhizal fungi contain chitin in their cell walls and may be influenced by transgenic chitinases. This study examined the ability of a transgenic tree, silver birch (Betula pendula Roth), constitutively expressing the sugar beet chitinase IV gene, to form ectomycorrhizae with Paxillus involutus (Batsch) Fr. Eight transgenic lines showing varying levels of sugar beet chitinase IV expression and the non-transgenic control plants were inoculated by P. involutus in vitro , and the morphology of the mycorrhizae,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 48 publications
2
12
0
Order By: Relevance
“…This demonstrates that for these EM fungal species, the transgenic chestnut does not appear to have any nontarget impacts. The result is consistent with studies that have demonstrated minimal to no impact on EM fungi by a number of transgenic tree species expressing a variety of transgenes (48)(49)(50)(51)(52). One such study, on a transgenic American elm expressing an antimicrobial peptide to improve Dutch elm disease resistance, found that there was no significant difference in mycorrhizal colonization during the field trial (53).…”
Section: Discussionsupporting
confidence: 75%
“…This demonstrates that for these EM fungal species, the transgenic chestnut does not appear to have any nontarget impacts. The result is consistent with studies that have demonstrated minimal to no impact on EM fungi by a number of transgenic tree species expressing a variety of transgenes (48)(49)(50)(51)(52). One such study, on a transgenic American elm expressing an antimicrobial peptide to improve Dutch elm disease resistance, found that there was no significant difference in mycorrhizal colonization during the field trial (53).…”
Section: Discussionsupporting
confidence: 75%
“…Pleiotropic effects from GM trees coexpressing such selectable markers have also been recorded. For example, Pasonen et al (56) showed a significant decrease in the number of root tips colonized by Paxillus involutus associated with a line of chitinase-transformed silver birch in vitro. Similar results have been observed in vivo with P. involutus associated with a line of lignin-modified silver birches (72).…”
mentioning
confidence: 99%
“…Crops, fruits, and forest trees exhibit mycorrhizal colonization by arbuscular mycorrhizae, ectomycorrhizae, and ectendomycorrhizae (EEM). While numerous studies have addressed the impact of transgenic plants on arbuscular mycorrhizae (10,26,64,68,72,73) and ectomycorrhizae (32,43,50,60), no previous study focused on EEM.…”
mentioning
confidence: 99%